G551D‐CFTR needs more bound actin than wild‐type CFTR to maintain its presence in plasma membranes. (8th April 2015) - Trouvé, Pascal; Kerbiriou, Mathieu; Teng, Ling; Benz, Nathalie; Taiya, Mehdi; Le Hir, Sophie; Férec, Claude
Abstract Cystic Fibrosis is due to mutations in the CFTR gene. The missense mutation G551D (approx. 5% of cases) encodes a CFTR chloride channel with normal cell surface expression but with an altered chloride channel activity, leading to a severe phenotype. Our aim was to identify specific interacting proteins of G551D‐CFTR which could explain the channel defect. Wild‐type CFTR (Wt‐CFTR) was co‐immunoprecipitated from stably transfected HeLa cells and resolved by 2D gel electrophoresis. Among the detected spots, one was expressed at a high level. Mass Spectrometry revealed that it corresponded to actin which is known to be involved in the CFTR's channel function. To assess whether actin could be involved in the altered G551D‐CFTR function, its basal expression was studied. Because actin expression was the same in wt‐ and in G551D‐CFTR expressing cells, its interaction with both wt‐ and G551D‐CFTR was studied by co‐immunoprecipitation, and we found that a higher amount of actin was bound onto G551D‐CFTR than onto Wt‐CFTR. The role of actin upon wt‐ and G551D‐CFTR function was further studied by patch‐clamp experiments after cytochalasin D treatment of the cells. We found a decrease of the very weak currents in G551D‐CFTR expressing cells. Because a higher amount of actin is bound onto G551D‐CFTR than onto Wt‐CFTR, it is likely to be not involved in the mutated CFTR's defect. Nevertheless, because actin is necessary to maintain the very weak global currents observed in G551D‐CFTR expressing HeLa cells, we conclude that more actin is necessary to maintain G551D‐CFTR in the plasma membrane than for Wt‐CFTR.